International Efforts and Next Steps to Advance COVID-19 Vaccines Research and Production in Low- and Middle-Income Countries - Li Du; Meng Wang; Vera Lúcia Raposo (Vaccines, 2021)
Equitable and efficient distribution of COVID-19 vaccines continues to be a key issue in global health, and a targeted approach is needed to meet the World Health Organization’s world vaccination targets. Although some low- and middle-income countries (LMICs) are developing their own vaccines to address the distribution problem, legal and technical challenges have had a negative impact on productivity. This article explores relevant international legal instruments that can enable faster research and development of COVID-19 vaccines in LMICs, focusing on the role of biosafety standards, biological materials transfer, and key knowledge sharing. Our analysis has established that the potential of existing global health legal instruments has yet to be realized in order to close the productivity gap in LMICs and strengthen their vaccine manufacturing capacity. Additionally, mutual recognition of vaccine efficacy has become a new challenge for achieving global vaccination targets. We argue that the World Health Organization should continue its leading position by developing a more practical and targeted framework to help LMICs overcome challenges arising from technology transfer, knowledge sharing, and politics.